The Effect Of Competency And Training On Performance Through Organizational Commitments To Village Apparatus - AnikRahma; Falih Suaedi; Erna Setijaningrum (Universitas Airlangga, 2022)
Village funds were a form of state recognition of villages. However, the authority received by the village government in village funds from the central government had not been matched by adequate human resources. It was one of the fundamentals behind the basic policies of the Indonesian Government as Village Government Administrators. Tuban Regency was one of the districts that received and distributed village funds where the Tuban Regency Government also did not escape the problems in distributing village funds, one of which was in Palang District, which could provide village fund distribution. This study aimed to analyzing and testing the effect of competency and training on the performance through organizational commitment of village apparatus in the village fund budget. This research used a quantitative approach with explanatory methods. This study concluded that: 1.) Competency has a significant positive effect on organizational commitment of village apparatus; 2.) Training has a positive effect but not significant on organizational commitment of village apparatus; 3.) Competency has a significant positive effect on the performance of the village apparatus; 4.) Training has a significant positive effect on the performance of the village apparatus; 5.) Organizational commitment has a significant positive effect on the performance of village apparatus; 6.) Organizational commitment to mediate the effect of competency on the performance of village apparatus positively but insignificantly; 7.) Organizational commitment to mediate the effect of training on the performance of village apparatus positively but insignificantly.